Fragmentasi Permukiman dan Kualitas Hidup di Global Selatan: Bukti dari Kecamatan Tugu, Kota Semarang - Fikri Arif Pradipta; I Dewa Made Frendika Septanaya (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Residential fragmentation has emerged as a critical challenge in rapidly urbanizing regions of the Global South, reflecting spatial and social segregation driven by disparities in socioeconomic status, access to infrastructure, and urban services. This study investigates the level of residential fragmentation in Tugu District, Semarang City, and examines its impact on the quality of life of residents in three residential types: gated communities (Graha Padma and Green Oase Homy Residence), formal housing (Jerakah and Tugurejo), and informal housing (Tugurejo, Randu Garut, and Mangunharjo). Using a mixed-methods approach, the study integrates quantitative and qualitative survey data from interviews, field observations, and secondary data. Descriptive statistical analysis is used to assess variations in quality of life indicators, while a SWOT analysis is applied to formulate strategic interventions. Findings reveal significant gaps in infrastructure access, environmental quality, security, and social interaction, where higher levels of fragmentation are associated with lower social cohesion and well-being; informal housing shows the highest vulnerability, while gated communities show better service provision but weaker social integration. Based on the findings, this study recommends specific strategies to enhance inclusivity, improve service accessibility, and social integration in fragmented residential areas. The proposed priority intervention is the integration of drainage systems across residential fragments, as issues of drainage, sanitation, and flood/tidal flood vulnerability are critical points that most influence residents' quality of life. Thus, in addition to enriching theories of urban fragmentation and resilience, this study offers practical policy directions for governments to reduce disparities in basic services while strengthening physical and social connectivity between residential types in secondary cities of the Global South.